A New Equation of State for Detonation Products of RDX‐Based Aluminized Explosives. Issue 10 (11th July 2019) - Liu, Yan; Wang, Hong‐fu; Bai, Fan; Huang, Feng‐lei; Hussain, Tariq
Abstract: In order to explain the detonation performance of RDX‐based aluminized explosives with different aluminum particle sizes, a new equation of state (EOS) for aluminized explosives is proposed. The proposed EOS regards the gasification of aluminum particles as a real reaction. The proposed EOS takes account of constituent aluminum particle sizes. The proposed EOS was implemented in LS‐DYNA as a user defined EOS and validated by simulating the experiments of metal plates acceleration caused by detonation of RDX‐based aluminized explosives. The numerical results reproduce the experimental finding that the reaction rate of aluminum particles increases with the decrease of aluminum particle size. The proposed EOS has several advantages over the previously reported equations of state for aluminized explosives. The reaction rate of aluminum constituents is calculated theoretically from their gasification reaction rate equation eliminating the need for experimental calibration of the corresponding empirical parameters. Abstract :